Supergraph based periodic pattern mining in dynamic social networks. (15th April 2017) - Halder, Sajal; Samiullah, Md.; Lee, Young-Koo
Highlights: We propose supergraph based single pass periodic pattern mining technique. This technique is polynomial unlike most graph mining problems. It is time consuming process because it stores all entities only once. Each time one sub-patterns calculation is needed that way it is memory efficient. It can predict human nature and attitude that are significant in various applications. Abstract: In dynamic networks, periodically occurring interactions express especially significant meaning. However, these patterns also could occur infrequently, which is why it is difficult to detect while working with mass data. To identify such periodic patterns in dynamic networks, we propose single pass supergraph based periodic pattern mining SPPMiner technique that is polynomial unlike most graph mining problems. The proposed technique stores all entities in dynamic networks only once and calculate common sub-patterns once at each timestamps. In this way, it works faster. The performance study shows that SPPMiner method is time and memory efficient compared to others. In fact, the memory efficiency of our approach does not depend on dynamic network's lifetime. By studying the growth of periodic patterns in social networks, the proposed research has potential implications for behavior prediction of intellectual communities.